2020
DOI: 10.3389/fvets.2020.00285
|View full text |Cite
|
Sign up to set email alerts
|

Coccidioides posadasii in a Dog With Cervical Dissemination Complicated by Esophageal Fistula

Abstract: A 5-year-old male, neutered mixed breed dog with a history of a mass with an associated draining tract on the ventral cervical region was diagnosed with an esophageal fistula. The dog exhibited serosanguinous discharge from the draining tract, with enlarged left superficial cervical and mandibular lymph nodes, and was reported to have difficulty with deglutition of solid foods. Computed tomography revealed a communication of the draining tract with the esophagus along with enlargement of the left lateral retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Investigation into the immunopathogenesis of this disease could provide insight into the wide spectrum of clinical manifestations in dogs with coccidioidomycosis [ 4 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. Guided by what has been learned from human clinical and mouse experimental studies, the primary objective of the study reported here was to compare constitutive and Coccidioides spp.…”
Section: Introductionmentioning
confidence: 99%
“…Investigation into the immunopathogenesis of this disease could provide insight into the wide spectrum of clinical manifestations in dogs with coccidioidomycosis [ 4 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. Guided by what has been learned from human clinical and mouse experimental studies, the primary objective of the study reported here was to compare constitutive and Coccidioides spp.…”
Section: Introductionmentioning
confidence: 99%
“…Lymphadenitis is defined as the presence of increased inflammatory cells within the lymph node and further defined by the predominant inflammatory cell type present [ 3 ]. Disseminated coccidioidomycosis, Coccidioides posadasii, was described in a canine with an oesophageal fistula and enlargement of the medial and lateral retropharyngeal lymph nodes [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…A deep neck abscess in humans has been described as an abscess or infection deeper than the superficial layer of the deep cervical fascia [6.] Underlying factors can include dental disease, tonsillitis, trauma, foreign body penetration into the oral cavity, neoplasia, or unidentified causes, which represent 20-50% of cases in humans [ 4 , 6 , 7 ]. Cervical abscesses in the dog can similarly be associated with trauma, foreign body penetration or migration, dental disease, or iatrogenic introduction via fine needle aspirates.…”
Section: Introductionmentioning
confidence: 99%